Enhancing the Development of Students’ Islamic Identity in Islamic Higher Education - Saddam Husein; Nik Md. Saiful Azizi Nik Abdullah; Dawood Abdulmalek Yahya Al-Hidabi (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2022)
The present study explores the role of the Institute for Islamic Studies and Practice (LPPI), Universitas Muhammadiyah Yogyakarta (UMY) in developing the students' Islamic identity. The study employed a qualitative case study design to capture the real-life context of LPPI UMY in playing its role. Through purposive sampling, the head of LPPI was selected as an informant in the study, considering his role and experiences leading this institution for about ten years. A depth semi-structured interview was conducted for data collection. The data were analyzed through thematic analysis to emphasize pinpointing, examining, and recording patterns (or “themes”) from the verbatim transcribed data. The findings revealed that LPPI UMY, as an institution mandated by the university to manage and develop Al-Islam dan Kemuhammadiyahan (AIK) for the entire academic community in UMY, plays its role in developing the Students' Islamic identity through two significant programs: Learning and Guidance Programs. Learning programs are conducted as courses inside the faculty's curricula and consist of four courses, AIK 1, 2, 3, and AIK 4. On the other hand, Guidance programs are conducted as extracurricular and formulated in the form of the scheme of character building through some stages of Islamic activities, as well as supported by other programs such as Ramadhan activities.